2004
DOI: 10.1073/pnas.0403606101
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an alternative ligand-binding pocket in the nuclear vitamin D receptor and its functional importance in 1α,25(OH) 2 -vitamin D 3 signaling

Abstract: T he steroid hormone 1␣,25(OH) 2 -vitamin D 3 (1,25D) (Fig. 1A), other steroid hormones, retinoids, and thyroid hormones form the family of ligands for the nuclear receptor (NR) superfamily (1), the members of which produce genomic responses through selective interaction of the liganded receptor with promoters of appropriate genes and basal transcription machinery. Many of these hormones also activate rapid, nongenomic (NG), cellular signaling cascades (2, 3) (except retinoids) that range from activation of io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
203
1
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 154 publications
(225 citation statements)
references
References 44 publications
19
203
1
2
Order By: Relevance
“…These results complement those of Ellison and colleagues, who showed that VDR-knockout mice are much more susceptible to photocarcinogenesis (44). The VDR has been shown to be essential for nongenomic effects of vitamin D compounds (9,10,13). In VDR-knockout mice, thymine dimer repair was significantly reduced (44 (44) is that photoprotection in mice seems to be mediated through a nongenomic pathway, which is still likely to involve the VDR but which may be activated by compounds other than the classical hormone (10).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…These results complement those of Ellison and colleagues, who showed that VDR-knockout mice are much more susceptible to photocarcinogenesis (44). The VDR has been shown to be essential for nongenomic effects of vitamin D compounds (9,10,13). In VDR-knockout mice, thymine dimer repair was significantly reduced (44 (44) is that photoprotection in mice seems to be mediated through a nongenomic pathway, which is still likely to involve the VDR but which may be activated by compounds other than the classical hormone (10).…”
Section: Discussionsupporting
confidence: 55%
“…Thus, the same 1,25(OH) 2 D 3 nuclear receptor (VDR) has been found in the plasma membrane caveolae of target cells where it is engaged in mediating nongenomic responses (9,10). The VDR ligand 1,25(OH) 2 D 3 is highly conformationally flexible, and it has been shown that one shape of 1,25(OH) 2 D 3 is preferred for genomic responses whereas another shape is preferred by the VDR for nongenomic responses (11)(12)(13). The 6-s-cis conformationally restricted analogue 1a,25(OH) 2 -lumisterol (JN) shows little ability to increase transcription of the osteocalcin gene in bone cells compared with 1,25(OH) 2 D 3 (14) but generates nongenomic actions in pancreatic b cells and endothelial cells (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…1C) [25]. The VDR A-pocket was discovered using in silico techniques and has been linked to shape and stereospecific induction of nongenomic cellular responses [26], as well as the unique structure-function results obtained for some A-ring and side-chain derivatives of 1,25D [27,28]. An important assumption made in these works is that the VDR A-pocket represents a kinetically favored ligand binding pocket (LBP), while x-ray results clearly indicate the VDR G-pocket is the thermodynamically favored LBP.…”
Section: Introductionmentioning
confidence: 99%
“…These include interaction of calcitriol with a membrane receptor, either a novel receptor or the known vitamin D receptor, thereby activating cell signalling pathways (Nemere and Campbell, 2000;Holick, 2003;Evans et al, 2004;Fleet, 2004;Mizwicki et al, 2004;Dusso et al, 2005;Hendy et al, 2006). There is growing direct evidence that the traditional vitamin D receptor may also have a unique, nontranscriptional role in plasma membrane initiated signalling (Fleet, 2004 (Berger et al, 1988;Sandgren et al, 1991;Rougui et al, 1998;Sheinin et al, 2000;Chatterjee, 2001;Holick, 2003;Lee et al, 2003).…”
mentioning
confidence: 99%